Evaluation Of Hydraulic Parameters Effects On The Stability Of Dike Embankment During Spatial Overtopping Tests - Hassan, Marwan Adil (2019)
River dike construction has been widely used because of its potential in protecting people and properties from overtopping flow. During high discharge of a river, water level may exceed a dike crest and causes overtopping flow. This phenomenon has caused a large damage on dike body due to the reduction of soil shear strength. This mechanism involved an increase in water content within particles and its relationship with the development of breach channel failure in downstream and upstream slopes are affected by a series of geotechnical and hydraulic aspects, such as inflow discharge, dike slope and soil type, caused by overtopping failure. These parameters had been investigated in this study through physical experiments and numerical modelling during overtopping failure. A series of 3D and 2D physical modelling is conducted on a homogeneous dike embankment under the effect of inflow discharge, dike slope angle and soil type parameters. The first phase focused on the development of pore water pressures and volumetric water contents for groups of points distributed along the upstream and downstream slopes of the dike embankment. Twelve tensiometer and time-domain reflectometer sensors were used to measure the magnitudes of negative pore water pressures (matric suction) and volumetric water contents. Physical experimental tests showed that a high inflow discharge resulted in a rapid increase in the amount of water content and a decrease in matric suction inside soil particles due to a high water velocity, whereas a gentle slope and coarse sand soil increased the rate of water saturation. The second phase of the experiment involved a 2D overtopping test to investigate the water level infiltration in vertical and horizontal directions during the transition of the water level from the toe of the upstream slope to the beginning of the dike crest. The dike body was more rapidly saturated by the horizontal water level than by the vertical water level. The velocity of the two water levels increased the initiation of the breach channel failure in the crest and the instability state in the upstream and downstream slopes. The third phase included the progression of vertical and horizontal erosion processes during the dike breach failure. Two digital cameras were installed in front of the dike body and the downstream slope to capture the mechanism of failure caused by erosion. The dominant failure in the pilot channel and the upper part of downstream slope was vertical erosion, and the progression of breach failure in the middle of the dike and the upstream slope occurs because of horizontal erosion. Transient seepage and slope stability analyses (FOS) were performed using 2D finite element methods and time-history measurements under the effect of dike slope angle and soil type. The numerical model was limited by its inability to mathematically incorporate all physical processes governing an overtopping breach failure. The Numerical analysis revealed that a steep slope and fine particles increased the pore water pressure and reduced the FOS. Appropriate dike design and maintenance were dependent on surrounding hydraulic conditions, dimensions and soil types. A gentle slope and noncohesive materials with fine particles were preferable.